2015
DOI: 10.1505/146554815817476459
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the economic impacts of trade liberalisation on forest products trade in the Asia-Pacific region using the GTAP model

Abstract: This chapter describes how we obtained the initial estimates for the Global Trade Analysis Project (GTAP) behavioral parameters file. These include the source substitution or Armington elasticities, the factor substitution elasticities, the factor transformation elasticities, the investment parameters, and the consumer demand elasticities. Table 14.1 summarizes for these parameters: the associated notation, the set over which they are indexed, and their description. In this chapter we explain the role of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It shows that the agreement can bring positive effects for both China and Australia. Stenberg and Siriwardana (2015) analysed the effects of unilateral trade liberalization of forest products on the Asia-Pacific Economic Cooperation (APEC) member countries and the result is the same as the previous study that countries engaged in international cooperation can gains benefits. Also, Padella et al (2012) examined the integrated impacts of the US and EU biofuels programs, regarding of socioeconomic effects on prices, employment and welfare in the European Union.…”
Section: Literature Reviewmentioning
confidence: 81%
“…It shows that the agreement can bring positive effects for both China and Australia. Stenberg and Siriwardana (2015) analysed the effects of unilateral trade liberalization of forest products on the Asia-Pacific Economic Cooperation (APEC) member countries and the result is the same as the previous study that countries engaged in international cooperation can gains benefits. Also, Padella et al (2012) examined the integrated impacts of the US and EU biofuels programs, regarding of socioeconomic effects on prices, employment and welfare in the European Union.…”
Section: Literature Reviewmentioning
confidence: 81%
“…In the absence of agreements, the projected tariff and non-tariff barriers are usually used to simulate the trade effects of the expected member countries (Park et al, 2021). Stenberg and Siriwardana (2016) examined the effects of trade liberalisation on forest products trade when APEC extend their preferential treatment to non-member countries using GTAP model. After the trade agreement has been signed, the tariff and non-tariff barriers calculated by the agreement are used to simulate the economic impact on the member countries, and then the changes of trade value in the future is calculated.…”
Section: Research On Green Trade Potential Predictionmentioning
confidence: 99%
“…Slater et al (2016) explored the consequences of these norms for viable ADLI execution in Sub-Saharan Africa (SSA). They found that while agriculture has significant solid areas for by and large in SSA, most countries don't fulfill the second proportions of spread out supply responsiveness (considering the way that the gathering creation limit is extremely confined, many kinds of purchaser stock are not made locally, and most intermediates and equipment are imported) (Stenberg & Siriwardana, 2015). From Figure 4, as the acknowledgment of agriculture for improvement relies upon rural development, this segment gives a concise contextualization of the writing on horticultural turn of events (Dastagiri et al, 2012).…”
Section: Figure 3 Economic Growth Due To Agriculture Classificationmentioning
confidence: 99%